Renewable energy resources in students’ opinions - Roman, Michał (Studia Ecologiae et Bioethicae, 2015)
The article aims to present the research findings regarding the level of knowledge the students of Warsaw University of Life Sciences and the students of Jadwiga Dziubińska Agricultural Education Centre Schools in Golądkowo have about renewable energy resources. The research shows that the university and secondary school students are most knowledgeable about solar energy and wind power. The students whose field of studies is Renewable Energy Technologies demonstrate more knowledge of geothermal energy, biogas or biomass. Most respondents acquire knowledge about renewable energy resources from the Internet and television while the students of Renewable Energy Technologies acquire their knowledge in the course of their studies. The respondents believe that the production of energy from renewable sources is safe for the environment and human health. But most respondents, including secondary school and university students, think that biogas is harmful to the environment and human health. Almost three fourth of the respondents are most willing to use solar energy. The second most popular source of energy is wind power. According to the respondents, the advantages of the investments are the protection of the environment and the reduction of greenhouse gases emission. A big proportion of the students of Renewable Energy Technologies are for becoming independent of the increasing prices of fossil fuels. The research shows that, in the students’ opinion, wind power and solar energy development is most prospective in Poland. The students of Renewable Energy Technologies believe that there are big opportunities for biomass development in Poland.